On the energy-bandwidth trade-off in green wireless networks: System level results - Butt, M. M.; Schubert, B.; Kurras, M.; Borner, K.; Haustein, T.; Thiele, L. (2012 1st IEEE International Conference on Communications in China Workshops, 2012)
Energy efficient communication is getting a lot of attention from the industry and academia due to high energy cost of operating mobile networks and their environmental effects. We discuss the self optimization aspect of the mobile network and evaluate the performance of power allocation strategy for the network at low load specifically where bandwidth efficiency is not as important. We propose trading of bandwidth for achieving high energy efficiency. We evaluate the impact of allocation of extra bandwidth in a lightly loaded cell on the overall network energy efficiency. The numerical results demonstrate the optimal load conditions when bandwidth expansion is useful for the network.